Analisis Pengaruh Gaya Visionary Leadership Dan Job Discipline Terhadap Worker Productivity Melalui Harmonious Work Sebagai Variabel Mediasi (Studi pada BEM FEB UNISMA) - Supardi, Fendi Prayogo All; Mustapita, Arini Fitria; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of visionary leadership style and job discipline on worker productivity with harmonious work as a mediating variable (case study at BEM Feb Unisma). The population used in this study were all administrators of BEM FEB UNISMA. The sample in this study amounted to 40 people obtained by the Purposive Sampling formula. The variables used in this study are worker productivity as the dependent variable, visionary leadership style, job discipline as independent variables, and harmonious work as a mediating variable. The results of this study are; the visionary leadership style variable does not have a positive and significant influence on worker productivity, the visionary leadership style variable has a positive and significant influence on harmonious work, the job discipline variable has a positive and significant influence on worker productivity, the job discipline variable has a positive and significant influence on harmonious work, the harmonious work variable has a positive and significant influence on worker productivity, the visionary leadership style variable has a positive and significant influence on worker productivity through harmonious work as a mediating variable, and the job discipline variable has a positive and significant influence on worker productivity through harmonious work as a mediating variable. Keywords: Worker Productivity, Visionary Leadership Style, Job Discipline, And Harmonious Work